(untitled) (Current Horticulture, 2024)
Arbuscular mycorrhizal fungi (AMF) are found in rhizosphere of citrus (Citrus spp.) crops to form mutualistic symbiosis with roots, arbuscular mycorrhizas. The AMF have been confirmed to increase plant growth, enhance nutrient acquisition and stress tolerance, improve fruit quality, and stabilize soil aggregation. Such roles of mycorrhizal symbiosis are an important part of the normal growth of citrus trees. However, low mycorrhizal colonization of roots is found in citrus grown in open field. The growth of AMF needs a good soil environment and supply of plant carbohydrates. On the other hand, some technologies of citriculture can also affect mycorrhizal growth and activity. The present mini review simply outlined mycorrhizal growth in roots, and paid attention to horizontal roots. Mycorrhizal roots of citrus require the characteristics of loose aeration, water-repellent, moist and slightly acidic soils. In addition, proper pruning and thinning of flowers and fruits, mulch, no tillage, enough sunlight, appropriate soil moisture and nutrient content, and mycorrhized seedlings at transplanting are collectively conducive to the growth and activity of arbuscular mycorrhizas. Some highlights regarding AMF management in citriculture are also briefly proposed.